1978
DOI: 10.1111/j.1365-2559.1978.tb01737.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of carcinoembryonic antigen in tissue sections with spread of mammary carcinoma

Abstract: An immunoperoxidase technique for the histological demonstration of Carcinoembryonic Antigen (CEA) was applied to paraffin sections from 74 breast carcinomas and 43 benign breast lesions. Sixty-six per cent of the carcinomas and the only case of granular cell myoblastoma examined were CEA positive. Two examples of mammary dysplasia (7%) showed foci of CEA positive acini. All tumour tissue found in lymphatics and in metastases in lymph nodes was CEA positive, including two cases where the primary tumour was CEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…The incidence of CEA positivity in breast carcinomas investigated immunohistochemically has ranged from 1.6% in one study [15] to 42-83% in others [4][5][6][7][8][10][11][12]. In our study 60% of the turnouts were CEA positive, in keeping with most of other reported series.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The incidence of CEA positivity in breast carcinomas investigated immunohistochemically has ranged from 1.6% in one study [15] to 42-83% in others [4][5][6][7][8][10][11][12]. In our study 60% of the turnouts were CEA positive, in keeping with most of other reported series.…”
Section: Discussionsupporting
confidence: 89%
“…However, studies using the immunoperoxidase technique to detect CEA in histologic sections of breast cancer have provided conflicting results. There are some publications in which CEA immunoreactivity in breast cancer was found to be correlated with a worse prognosis [4][5][6][7][8] whereas other authors [9][10][11][12] failed to find this correlation. None of these studies have had a population of patients with a well-defined clinical stage and long-term follow-up.…”
Section: Introductionmentioning
confidence: 93%
“…Van der Linden et al [6] also did not find any correlation be tween the presence of immunoreactive CEA and the binding of the lectin peanut agglu tinin to tumor cells in primary/metastatic breast cancer. On the contrary, Shousha and Lyssiottis [7] studied tissue CEA by the im munoperoxidase technic and found a signifi cant relationship between CEA positivity in primary tumor and the presence of lymph node métastasés. Therefore, from this and previous investigations [4,8], it was sug gested that plasma CEA is an 'adenocarcino ma-associated antigen' instead of a 'tumorassociated antigen' because CEA levels were not elevated in the tumors derived from ectoderm as compared with tumors of endodermal origin.…”
Section: Discussionmentioning
confidence: 98%
“…Carcinoembryonic antigen (CEA) [61] may be useful as the first step in an immuno peroxidase study of undifferentiated medias tinal tumors ( fig. 8).…”
Section: What Kinds Of Controls Are Needed?mentioning
confidence: 99%